Penerapan Metode Multi-Factor Evaluation Process dalam Keputusan Pemilihan Hewan Pemeliharaan untuk Anak - Ghufriyyah, Shinta; Adelia, Tsania Shidqi; Muzid, Syafiul (Jurnal Informatika Terpadu, 2025)
The selection of suitable pets for children requires consideration of several criteria, including gentle temperament, care needs, safety, and social interaction. This study applies the Multi-Factor Evaluation Process (MFEP) method to recommend the most appropriate pets for children based on predefined criteria. MFEP is a decision-making technique that determines preference values by weighting each criterion and evaluating performance scores. A quantitative approach was employed with five pet alternatives and five evaluation criteria: safety, interaction level, care cost, ease of maintenance, and allergy potential. The evaluation results show that ornamental fish achieved the highest preference score of 0.92, followed by turtles with 0.87, indicating their suitability as ideal pets for children. These findings demonstrate that the MFEP method supports structured and objective decision-making in pet selection. Future studies are recommended to include additional criteria tailored to children’s specific needs, such as allergies or physical limitations.